EP1119 Fischer rate 344 with syngeneic epithelial ovarian cancer (EOC) cells NuTu 19: key points for building a reliable ovarian carcinomatosis animal model. (1st November 2019) - Dupré, PF; Muller, M; Le Gall, T; Loisel, S; Montier, T
Abstract : Introduction/Background: Animal models are required for better understanding of EOC natural history and therapy assay. We set up an experimental peritoneal carcinomatosis in an immunocompetent female rat model Fischer F 344 using a syngeneic epithelial ovarian cancer cell line NuTu 19. Methodology: Twenty height female Fischer rats' F 344 were used in keeping with ethical in animal testing. NuTu19 were transfected using the lipophosphoramid KLN-47 reagent carrying the luciferase-encoding plasmid pTG11033. NuTu 19 Luc+ cells were injected into the peritoneum in the left iliac fossa with various concentration and dilution. Bioluminescence monitoring was performed day 4, 10, 17, 25, 31, 38 and 49. Surgery was performed under general anesthesia and pain management at day 17, 31, 49, 77. Two Peritoneal Carcinomatosis Index (PCI) were used. Results: Significant luciferase-activity was observed 24 hours following the injection, increased gradually and stabilising from day 10 (table 1). Site-injection and sub-diaphragmatic areas were the two most common bioluminescent locations whatever cell concentration. Macroscopic tumour graft was found delayed at day 21 and Iterative surgery show increasing PCI over time. Medium PCI 1 was 22.5 [17–41] and PCI 2 22 [13–29]. Pathological exam (PE) was performed in 21 rates and results did not correlate with PCI and bioluminescence. Lymphoid hyperplasia without carcinomatosis was found for low PCI (<6) in four rates, however high PCI (>12) were associated with tumour graft at PE. No carcinomatosis was found at PE before day 10 and bioluminescence's positive predictive value was 62.5% from day 35. Conclusion: Developing a non-short term -life-threatening microscopic homogeneous carcinomatosis remains a challenge for in-vivo therapy assay. The choice of a suitable animal model for surgery requires high quality experimental plan and systematic sampling for pathological exam to avoid incorrect assessment. Disclosure: Nothing to disclose